DESAIN PEMBELAJARAN BILANGAN MENGGUNAKAN KONTEKS PERMAINAN LAYANG-LAYANG - Syutaridho, Syutaridho; Zulkardi; Ratu Ilma Indra Putri; Elly Susanti; Duano Sapta Nusantara (Jurnal Pendidikan Matematika RAFA, 2023)
A learning process is said to be good if learning is student-centered. Students perform activities in the learning process by using context as a starting point in learning. Design Research with a cycle that contains components of knowledge (K), design (D), experiment (E), reflection (R) is an alternative to create student-centered learning and obtain information and findings in research. This research was conducted in one of the junior high schools in Palembang City with a sample of 23 students. Research procedures were carried out including observation data analysis, interviews and documentation analysis. The conclusion of this research is that the existing knowledge of students is used as a basis for designing learning activities so that when implementing experiments students are able to carry out activities that are related to the initial abilities of students so that the context appears to be a strating point in learning so that the findings that arise can be analyzed and become a reflection to carry out cycles. Then the effectiveness of learning goes according to design and produces a series of understanding of numbers and also the situation of "pulling" and "stretching" in the kite game can be converted into "positive and "negative" symbols